Comparative Usefulness of Sepsis-3, Burn Sepsis, and Conventional Sepsis Criteria in Patients With Major Burns. Issue 7 (July 2018) - Yoon, Jaechul; Kym, Dohern; Hur, Jun; Kim, Youngmin; Yang, Hyeong-Tae; Yim, Haejun; Cho, Yong Suk; Chun, Wook
Abstract : Objectives: We evaluated the ability of new sepsis (S3) criteria (compared with previous definitions of sepsis [S1] and burn sepsis criteria) to accurately determine the mortality in severe burns patients with sepsis. Design: This was retrospective cohort study. Setting: The Burn ICU of Burn Center, Hangang Sacred Heart Hospital, Hallym University, Seoul, Korea. Patients: A total of 1, 185 adult patients (mean age, 49.1 yr) were admitted between January 2009 and December 2015. Interventions: The 1, 185 patients enrolled in the present study and were then re-evaluated based on S1, burn sepsis, and S3 criteria, following which 565 patients, 812 patients, and 809 patients were diagnosed with sepsis based on S1, burn sepsis, S3 criteria, respectively. Measurements and Main Results: For diagnostic performance, sensitivity, specificity, predictive value, and likelihood ratio were calculated. The area under the curve of the receiver operating characteristic curve was calculated to determine the accuracy of mortality prediction. The optimal cutoff value of Sequential Organ Failure Assessment score was calculated by the decision tree method. Total body surface area burned was 33.4%. Patients were identified with sepsis using S1 (812), S3 (809), and burn sepsis (565) criteria. Overall mortality was 20.3%, highest (82.2%) and lowest (26.5%) occurred with new septic shock (SH3) and S3, respectively. The sensitivity and specificity for burn sepsis (84.6% and 61.8%) and SH3 (63.1% and 96.5%) were reported. Area under the curve values for Sequential Organ Failure Assessment scores were the highest in all sepsis categories. With Sequential Organ Failure Assessment score greater than or equal to 6 (with infection), the accuracy was 0.86 (95% CI, 0.82–0.89). Conclusions: The S3 criteria failed to show superior prognostic accuracy for mortality in severely burned patients. Sequential Organ Failure Assessment score greater than or equal to 6 may be a better criterion for the diagnosis of sepsis in burns patients.